Kedudukan Notaris Sebagai Turut Serta Dalam Tindak Pidana Korupsi - Ayu Pratiwi (Officium Notarium, 2022)
The modus operandi of corruption can be carried out in various ways so that the crimes committed can run smoothly, one of which involves a position that has certain authority, namely the Position of Notary. The final product of a notary is an authentic deed regarding legal actions, agreements, stipulations and legal events. A notary deed can be in the form of a partij deed or a relaas deed, in this case the notary is not a party to the deed, the function of the notary is only to formulate the will of the parties into the deed in accordance with the applicable provisions. Based on these problems, this research method is normative or doctrinal, the object of which is statutory regulations with a case and doctrine approach, then the primary legal materials are statutory regulations and secondary legal materials are books and journals. The results of this research are: it is inappropriate to label thethe notary's position as participant in the criminal act of corruption along with the deed that they made since the notary is not a party to the said deed and the making of the notary deed is only based on formal truth and the cause of the notary being in the vortex of corruption cases is the discrimination of notaries and the lack of knowledge of notary law by the law enforcement officials. The author's suggestion is that the authority of a Notary should be expanded like a judge in digging up material truth in the trial of a case.Key Word: Participation, Notary, Corruption Crime AbstrakModus operandi tindak pidana korupsi dapat dilakukan dengan berbagai cara supaya kejahatan yang dilakukan dapat berjalan mulus, salah satunya melibatkan suatu jabatan yang memiliki kewenangan tertentu yaitu Jabatan Notaris. Produk akhir Notaris adalah akta otentik mengenai perbuatan hukum, perjanjian, penetapan dan peristiwa hukum. Akta Notaris dapat berbentuk partij akta atau relaas akta, dalam hal ini Notaris adalah bukan pihak dalam akta, fungsi Notaris hanya menformulasikan kehendak para pihak kedalam akta sesuai ketentuan yang berlaku. Berdasarkan permasalahan tersebut metode penelitian ini adalah normatif atau doktrinal yang objeknya adalah peraturan perundang-undangan dengan pendekatan kasus dan doktrin kemudian bahan hukum primer adalah peraturan perundang-undangan dan bahan hukum sekunder ialah buku serta jurnal. Hasil penelitian ini kedudukan Notaris sebagai turut serta dalam tindak pidana korupsi sepajang terhadap akta yang dibuatnya adalah tidak tepat atau bukan pihak dalam perkara tersebut sebab Notaris bukan merupakan pihak dalam akta serta dalam membuat akta Notaris hanya berdasarkan kebenaran formal dan penyebab Notaris berada dalam pusaran kasus korupsi adalah kriminasisi Notaris dan rendahya ilmu hukum kenotariatan aparat penegak hukum. Saran penulis adalah sudah keyogyanya kewenangan Notaris diperluas layaknya hakim dalam menggali kebenaran materiil dalam persidangan suatu perkara.Kata-kata Kunci: Turut Serta, Notaris, Tindak Pidana Korupsi